Os recursos de acessibilidade comunicacional e a eficácia do processo de comunicação formal no ensino superior: proposição de guia multiformato - Santos, Ana Rita Rodrigues dos (2023)
This research aims to design a multi-format guide according to communication accessibility techniques and procedures, in the dissemination of information about student support service offered at the Federal University of Rio Grande do Norte (UFRN). In this proposition and with the support of a multidisciplinary team, efforts converge towards the design of a guide that reduces and/or overcomes noise in the communication process between UFRN and the university community. The problem that gave rise to this investigation relates to the effects produced by noise sources, empirically evidenced in the formal communication process between UFRN and its users. Thus, the research's guiding question is the following: how can a multi-format guide, based on the Inclusive Design approach, be a contributing factor in reducing communication noise levels? This is a qualitative exploratory and descriptive study, whose approach included the application of multi-methods for systematic data triangulation, combining scientific and empirical evidence. Regarding the literature review, the methodological procedures of Scope Review Survey (SR) are supported according to research approach of an operational nature, using design methods and tools for conception of a multi-format guide. Focus groups, co-creation dynamics, sociodemographic/academic/professional questionnaire and usability tests were used as data collection instruments. The project was submitted to the UFRN Ethics Committee, and the study participants signed the Free and Informed Commitment Term (FICT). For systematization, analysis and description of the data, the thematic content analysis techniques and procedures were used. The designed artifact, with the Inclusive Design approach, meets the requirements identified in this research, considering the diversity and specific needs of users. The data produced from this study effectively contribute to the production of knowledge, particularly in Education, with emphasis on topics related to communication accessibility, thus incorporating operational and administrative innovations on the university campus.